Spatial differences, distributional dynamics, and driving factors of green total factor productivity in China - Zhao, Peiyang; Wu, Haiyan; Lu, Zhiguo; Kou, Jiali; Du, Jun (Frontiers in Environmental Science, 2022)
Green total factor productivity (GTFP) is a major driver of environmental governance, climate change mitigation, and green transformation in China. This study aims to improve GTFP, reduce regional differences, and promote sustainable development. Herein, the slacks-based measure-global Malmquist–Luenberger index was used for the scientifically rigorous measurement of China’s GTFP from 2000 to 2019. Dagum’s Gini coefficient decomposition and kernel density estimation methods were used to explore GTFP regional differences and distributional dynamics. Finally, spatial GTFP heterogeneity driving factors were analyzed using a geodetector tool. We found that China's GTFP is on an overall upward trend, driven mainly by technological progress. There were substantial spatial differences in China’s GTFP, primarily caused by transvariation intensity, the average contribution of which is 43.26%. Differences in GTFP between and within regions decreased to varying degrees over time. Spatial heterogeneities in China’s GTFP were primarily caused by driving factors interactions, which were stronger than their individual effects. Thus, we recommend that China should accelerate the establishment of a new coordinated regional development mode, improve its green technology innovation capacity, increase openness, and push for a green model of development.